2004
DOI: 10.1080/00224490409552246
|View full text |Cite
|
Sign up to set email alerts
|

Condom use self‐efficacy among U.S.‐ and foreign‐born Latinos in Texas

Abstract: The objective of this study was to assess the influence of condom use self-efficacy on the reported condom use of Latinos. We conducted a rapid needs assessment study among U.S. and foreign-born Latinos living in Houston, TX, to identify behavioral and psychosocial factors that influence their risk for HIV. Bilingual Latino interviewers conducted confidential face-to-face interviews with individuals living in apartment complexes or residential areas primarily populated by Latinos. A total of 152 participants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 29 publications
2
26
0
5
Order By: Relevance
“…Estos resultados son similares a los obtenidos por Greig et al (2008) y Pulerwitz et al (2002, donde se concluye que tener poder en la relación implica un mayor uso del preservativo. Además, otros estudios explican el bajo uso del preservativo a partir del bajo poder en la relación de las mujeres (Fernández-Esquer et al, 2004;Harvey et al, 2002). Concretamente, aquellas mujeres con relaciones donde sus parejas tienen mayor poder y control, presentan mayor consumo de drogas (Jewkes, Dunkle, Nduna y Shai, 2010), más probabilidades de padecer, al menos, un tipo de disfunción sexual y menor satisfacción sexual (Lau et al, 2006), mayor probabilidad de suicidio (Canetto, 2008) y mayor probabilidad de ser infectadas por el VIH y otras ITS (Bermúdez, Castro, Gude et al, 2010;Herrera y Campero, 2002;Pulerwitz y Barker, 2008).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Estos resultados son similares a los obtenidos por Greig et al (2008) y Pulerwitz et al (2002, donde se concluye que tener poder en la relación implica un mayor uso del preservativo. Además, otros estudios explican el bajo uso del preservativo a partir del bajo poder en la relación de las mujeres (Fernández-Esquer et al, 2004;Harvey et al, 2002). Concretamente, aquellas mujeres con relaciones donde sus parejas tienen mayor poder y control, presentan mayor consumo de drogas (Jewkes, Dunkle, Nduna y Shai, 2010), más probabilidades de padecer, al menos, un tipo de disfunción sexual y menor satisfacción sexual (Lau et al, 2006), mayor probabilidad de suicidio (Canetto, 2008) y mayor probabilidad de ser infectadas por el VIH y otras ITS (Bermúdez, Castro, Gude et al, 2010;Herrera y Campero, 2002;Pulerwitz y Barker, 2008).…”
Section: Discussionunclassified
“…Este dato es similar a los obtenidos en diversas investigaciones (Bermúdez, Castro, Gude et al, 2010;Kreager y Staff, 2009 Por otra parte, se encuentra que el grupo de varones muestra una mayor adhesión a la doble moral y, en función de ésta, tratarían de mantener relaciones sexuales desprotegidas. Se puede concluir que, en mujeres, la única variable, de las analizadas en este estudio, que predice un mayor riesgo de infección por VIH, es el poder en la relación de pareja, tal y como encuentran otros autores (Fernández-Esquer et al, 2004;Kreager y Staff, 2009;Pulerwitz y Barker, 2008).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Parrado (2005) found that a woman's lower educational level was associated with less power over emotional control in sexual negotiations and a greater dependency on their male sex partner's determination, without significant differences between contexts. At the same time, findings of studies about individual attributes (that did not consider the interaction of sex partners) suggest that the migrants' higher educational level may be associated with a greater perception of risk, thereby favoring the use of condoms for preventive reasons (Fernandez-Esquer et al 2007;Organista et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In a study among university students in Texas communicated the regrets about their decision to engage in sexual activity and use condoms on the grounds of moral values [16]. Similarly, the denial of moral values while promoting condom use led to ignorance of use during the sexual intercourse in a study among the drug users in Texas [17]. This implicates that normative beliefs and subjective norms affects adversely the lifetime condom use and selfefficacy in condom use.…”
Section: Introductionmentioning
confidence: 99%